Regenerating Goong Renteng Panggugah Manah: Multi-Layered Enculturation in a Sundanese Tradition - Abizar Algifari Saiful; Rita Tila; Reyhan Swarna Medica (Universitas Negeri Surabaya, 2026)
Goong Renteng Panggugah Manah is a Sundanese karawitan ensemble of more than two centuries old, located in Sukamulya Village, Cigugur Subdistrict, Kuningan Regency, West Java. As a sacred gamelan inherited from Abah Raksajaya and acquired in 1792, this group faces sustainability challenges amid the currents of modernization and the shifting interest of younger generations toward popular music. This study aims to analyze the regeneration process taking place within the Goong Renteng Panggugah Manah arts group. The research employs a qualitative-ethnographic approach through participant observation, in-depth interviews with cultural practitioners, and documentary study. The findings reveal that regeneration occurs through three principal pathways, namely the kinship pathway of the Raksajaya family, the community pathway involving students and the general public, and the institutional collaboration pathway. These findings contribute to the discourse on community-based traditional music preservation in Indonesia.